Answer:
Step-by-step explanation:
<u>Use of formula:</u>
- P(A and B) = P(A)*P(B|A) and
- P(A and B) = P(B)*P(A|B)
<u>According to above and based on given:</u>
- P(A)P(B|A) = P(B)P(A|B)
- P(B|A) = P(A|B)*P(B)/P(A)
- P(B|A) = 0.20*0.40/0.25 = 0.32
Answer:
For this case we know that represent the radius, the height and the rate given is:
And replacing we got:
And that represent
Step-by-step explanation:
For a tank similar to a cylinder the volume is given by:
For this case we know that represent the radius, the height and the rate given is:
For this case we want to find the rate of change of the water level when h =6m so then we can derivate the formula for the volume and we got:
And solving for we got:
We need to convert the rate given into m^3/min and we got:
And replacing we got:
And that represent
Answer: pretty sure it’s because the left and bottom sides add up to equal the top side
Step-by-step explanation:
parallel lines have the same slope
The slope-intercept form of a linear equatio is y=mx+b, where m stands for the "slope of the line" and b stands for the "y-intercept of the line"
They give you the equation y= -5/6x+3 Notice this is already on the slope-intercept form, so in this case the slope is -5/6 and the y-intercept is 3
You want an equation of the line that is parallel to the given line. The slopes must be the same, so m=-5/6
So far we have y=-5/6x + b
We don't have b yet but that can be found using the given point (6,-1) which tells you that "x is 6 when y is -1"
Replace that on the equation y=-5/6x + b and you get
-1 = (-5/6)(6) + b
-1 = -5 +b
4 = b
b = 4
We found b, or the y-intercept
Go back to the equation y = -5/6 x + b and replace this b with the b we just found
y = -5/6x + 4
Answer:
X 1 = -4,X 2 =12
EXPLANATION:
Determine the defined range
X+6/x=6/x-8,x#0,x#8
Simplify the equation using cross-multiplication
(X+6) x (x-8)=6x
Move variable to the left-hand side and change its sign
(X-6)x(x-8)-6x=0
Multiply the parentheses
X^2-8x+6x-48-6x=0
Since two opposites add up to zero, remove them from the expression
X^2-8x-48=0
Write -8x as a difference
X^2+4x-12x-48=0
Factor out x from the expression
Xx(x+4)-12x-48=0
Factor out -12 from the expression
Xx(x+4)-12(x+4)=0
Factor out from the expression
(x+4)x(x-12)=0
When the product of factors equals 0, at least one factor is 0
x+4=0
x-12=0
Solve the equation for x
X=-4
X-12=0
X=-4,x#0,x#8
Check if the solution is in the defined range
X=-4
x=12
The equation has 2 solutions
X 1 = -4,X 2 =12
Hope this helps